2006
DOI: 10.1016/j.gassur.2005.08.036
|View full text |Cite
|
Sign up to set email alerts
|

Oncolytic Herpes Viral Therapy is Effective in the Treatment of Hepatocellular Carcinoma Cell Lines

Abstract: Introduction-The rising incidence of hepatocellular carcinoma (HCC) in western countries, along with the poor prognosis offered by present-day treatment modalities, makes novel therapies for this disease necessary. Oncolytic herpes simplex viruses (HSV) are replication-competent viruses that are highly effective in the treatment of a wide variety of experimental models of human malignancies. This study seeks to investigate the effectiveness of oncolytic herpes viruses in the treatment of primary hepatocellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…This differential in infectivity may be attributed to the overexpression of glypican-3 (GPC3) which is a cell surface heparin sulfate proteoglycan required by the HSV-1 viruses for adsorption (43). Increasing studies have reported on the use of replication-competent HSV-1 against hepatocellular carcinoma (44,45) and hepatic metastases (46). We and others (47,48) have shown that replication-defective HSV-1 amplicon viral vectors are equally efficient in delivering genes to the cells of hepatic origin.…”
Section: Discussionmentioning
confidence: 99%
“…This differential in infectivity may be attributed to the overexpression of glypican-3 (GPC3) which is a cell surface heparin sulfate proteoglycan required by the HSV-1 viruses for adsorption (43). Increasing studies have reported on the use of replication-competent HSV-1 against hepatocellular carcinoma (44,45) and hepatic metastases (46). We and others (47,48) have shown that replication-defective HSV-1 amplicon viral vectors are equally efficient in delivering genes to the cells of hepatic origin.…”
Section: Discussionmentioning
confidence: 99%
“…SNU-354, SNU-739, HepG2 cell lines are not tumorigenic (15). The AFP and TGF-β1, which represent the aggressiveness of the cell lines, were determined by immunoassay from the supernatant (16)(17)(18). AFP is expressed only in HepG2 and Hep3B.…”
Section: Hcc Cell Linesmentioning
confidence: 99%
“…Sia et al, [170] used as a viral vector the HSV-1 amplicon in HCC and non-HCC cell lines in vitro and in vivo with promising results. Several other reports characterized different kinds of HSV-1 vectors as platforms for virotherapy against liver cancer [167,168,[171][172][173].…”
Section: Inhibition Of Oncogenes and Restoration Of Tumor-suppressor mentioning
confidence: 99%